Causes and circumstances of accidents at work in the European Union, Slovakia and Czech Republic - Hollá, Katarína; Ďad'ová, Alena; Hudáková, Mária; Valla, Jirí; Cidlinová, Anna; Osvaldová, Linda Makovická (Frontiers in public health, 2023)
There are several challenges in occupational safety and health that need to be addressed. The basic premise is the reduction of occupational accidents in individual sectors. Finding effective tools to reduce them is very challenging. Safety culture is perceived differently in the countries of the European Union. The basic intention of this article is to compare the accidents number in these two countries and in the European Union in selected NACE categories. This comparison is based on the statistical processing of data by NACE category and representation of accident rates in individual industries. The main causes of accidents were identified, which give space for further research in this field a state measures to prevent work accidents to happen or to reduce its numbers.
Keywords: rizikové faktory; Česká republika; Accidents, Occupational; pracovní nehody; Risk Factors; Slovakia; Slovenská republika; Evropská unie; Czech Republic; European Union